Logística verde no transporte de carga no Brasil - Vieira, Letícia Borges (Universidade Federal de São Carlos, 2024)
The effects of climate change are being felt around the world. Caused by the emission of polluting gases into the atmosphere from anthropogenic activities such as the burning of fuels in transportation, industry, power generation and deforestation, companies are being held responsible and pressured to improve energy efficiency and find ways to mitigate or minimize the damage caused by their activities, especially logistics. In 2010, activities such as transportation accounted for 23% of global CO2 emissions. Although Brazil is a developing country with continental dimensions and diverse natural resources, the country has been disappointing in its sustainability metrics, ranking fifth among the largest climate polluters. This is because cargo transportation is based on the highest specific emissions mode, road transport, which in turn depends mostly on fossil fuels, which are non-renewable and highly polluting. In this way, the possibility of achieving lower emission levels can be seen by optimizing the country's cargo transport sector through strategies that culminate in the green logistics philosophy. With the advent of Industry 4.0, we can count on the support of technology to obtain data, analyze it and make decisions based on it - specifically to optimize routes, schedule movements, monitor fuel consumption and manage metrics. There is a growing body of research in the field of green logistics, with a focus on the use of alternative fuels, intermodal transfers, and infrastructure improvements in road, waterway and railway systems, each with its own specificities and challenges, and all under the supervision and regulation of organizations and the state through policies, taxes, and/or transactions in the carbon market.
Green logistics transportation in Brazil
Keywords: Transporte de cargas; Logística verde; Brasil; Cargo transportation; Green logistics; Brazil; CIENCIAS EXATAS E DA TERRA::QUIMICA